A History of Education for the Many From Colonization and Slavery to the Decline of US Imperialism - Malott, Curry (Radical Politics and Education, 2021)
Offering a novel take on the history of education in the US, A History of Education for the Many examines the development of the education system from a global and internationalist perspective. Challenging the dominant narratives that such development is the product of either a flourishing democracy or a ruling-class project to reproduce structural inequalities, this book demonstrates the link between education and the struggles of working-class and oppressed peoples inside and outside the US. In a country notorious for educating its people with an inability to see beyond its own borders, this book offers a timely corrective by focusing on the primacy of the global balances of forces in shaping the history of US education. Combining Marx's dialectic with W.E.B. Du Bois' historiographical approach, Malott demonstrates how the mighty agency of the world's poor and oppressed have forced the hand of the US ruling class in foreign policy and domestic educational policies. Malott offers a unique view of the dialectical development of social control by examining the role of the police and state violence, along with education or ideology over time. This situates the 2020 uprisings against racism and the movements to defund the police within a historical context dating back to eighteenth-century slave patrols. As US imperialism declines in the 21st century and social movements across the globe continue to swell and intensify, Malott's historical analysis looks backwards as it pushes us, optimistically and realistically, forwards towards a liberated future. The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 license on bloomsburycollections.com.